Fostering 4.0 Digital Literacy Skills Through Attributes of Openness: A Review - Chiappe, Andrés; Díaz, Juan Manuel; Ramirez-Montoya, María Soledad (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
During the last decade, a growing interest in open educational resources (OER) has developed among educational researchers worldwide. This trend involves the examination of possible effects over diverse learning domains such as the development of literacy and digital skills in the context of the fourth industrial revolution. To address this matter, a systematic literature review was conducted using PRISMA processes on 62 research articles published in high-impact peer-reviewed journals indexed in two major academic databases (Scielo and Scopus). Data collected during this literature review showed certain conditions that must be met to ensure a successful learning setup when OER are involved. Moreover, qualitative analysis revealed that certain attributes of openness are often more influential than others in the development of adequate literacy skills for the artificial intelligence era; also, there is an overall positive perception, from students and teachers alike, about the introduction of the attributes of openness and open materials into learning practices.